2013
DOI: 10.1016/j.ccr.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomic Analyses Reveal an Androgen-Driven Somatic Alteration Landscape in Early-Onset Prostate Cancer

Abstract: Early-onset prostate cancer (EO-PCA) represents the earliest clinical manifestation of prostate cancer. To compare the genomic alteration landscapes of EO-PCA with "classical" (elderly-onset) PCA, we performed deep sequencing-based genomics analyses in 11 tumors diagnosed at young age, and pursued comparative assessments with seven elderly-onset PCA genomes. Remarkable age-related differences in structural rearrangement (SR) formation became evident, suggesting distinct disease pathomechanisms. Whereas EO-PCAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
373
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 294 publications
(395 citation statements)
references
References 56 publications
(84 reference statements)
15
373
0
1
Order By: Relevance
“…We have previously used a break-apart FISH probe to demonstrate presence of PTEN breakage in 4% (including cases with simultaneous deletion of the remaining allele) of prostate cancers using a large prostate cancer prognosis tissue microarray containing a single tissue microarray core per donor tumor. 16 The results of our current heterogeneity study suggest that PTEN breakage may be much more frequent (18%), but may be a transient event during the development of complete PTEN loss. This assumption is based on the observation that all tumor foci with PTEN rearrangements also had tissue spots with partial and/or complete deletion of the broken PTEN allele, which can only be explained by initial PTEN breakage and subsequent deletion of chromosomal material flanking the breakpoint.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…We have previously used a break-apart FISH probe to demonstrate presence of PTEN breakage in 4% (including cases with simultaneous deletion of the remaining allele) of prostate cancers using a large prostate cancer prognosis tissue microarray containing a single tissue microarray core per donor tumor. 16 The results of our current heterogeneity study suggest that PTEN breakage may be much more frequent (18%), but may be a transient event during the development of complete PTEN loss. This assumption is based on the observation that all tumor foci with PTEN rearrangements also had tissue spots with partial and/or complete deletion of the broken PTEN allele, which can only be explained by initial PTEN breakage and subsequent deletion of chromosomal material flanking the breakpoint.…”
Section: Discussionmentioning
confidence: 62%
“…Next-generation sequencing studies performed by us 16 and others 22 revealed that PTEN can be disrupted by chromosomal breakage, resulting in partial deletions, inversions or translocations. We have previously used a break-apart FISH probe to demonstrate presence of PTEN breakage in 4% (including cases with simultaneous deletion of the remaining allele) of prostate cancers using a large prostate cancer prognosis tissue microarray containing a single tissue microarray core per donor tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades several drivers for prostate cancer and progression were identified at the genomic, transcriptional and protein-level [119,[173][174][175][176][177][178][179][180][181][182]. The acquisition of these driver mutations and subsequent tumor progression could either follow a linear pathway or a molecular diversity model as suggested by Rubin et al, 2011 [178].…”
Section: Genetic Drivers Signaling and Microenvironment In Prostate mentioning
confidence: 99%
“…Global gene expression profiling further shows that the AR is one of several genes to be consistently up-regulated in castrationresistant prostate cancer (CRPC) (7,8), which directly underscores the significance of androgen signaling in disease progression. Additionally, recent integrative genomic analysis revealed a significant enrichment of androgen signaling in early-onset prostate cancers, but not in elderly onset prostate cancers (9), further highlighting the significance of AR across the prostate tumorigenesis spectrum. The phosphatidylinositol (3,4,5)-phosphate kinase (PI3K) signaling pathway plays a critical role in human tumorigenesis, including prostate cancer (10).…”
mentioning
confidence: 99%